Herbomineral Toothpaste: A Novel Formulation for Dental Caries – An In Vitro Study (Asian Journal of Pharmaceutics (AJP), 2022)
Background: The demand for a broad spectrum antimicrobial toothpaste is highly desirable to reduce, control,and prevent various types of dental diseases. Therefore, research into the production of herbal toothpaste tosuppress the incidence of dental diseases is pertinent. Plant-based tooth paste has proved to be best at treating thegingivitis and other oral problems. Aim: In the present study, the herbomineral tooth paste was prepared using18 different herbal ingredients which possess different uses both internally and externally and also four mineralsalts that help to avoid tooth decay and gingival inflammation. The formulated toothpaste was evaluated forphysicochemical properties and anti-bacterial activity. Methodology: Three different formulations were preparedand evaluated for various physicochemical properties such as stability, pH, homogeneity, compatibility withtoothpaste packaging material, spreadability, abrasiveness, foaming ability, cleaning ability, and anti-bacterialactivity that was tested on two bacteria, Staphylococcus aureus strain (MTCC 96) and Streptococcus mutans strain(MTCC 890) in comparison with commercial formulation, Vicco Vajradanth. Results: All the results of evaluatedparameters showed that experimental formulation (F3) was comparably equal and better when compared withcommercial formulation in terms of standards specified by the Bureau of Indian Standards 6356–1993 and foundto be of good quality. The results were analyzed using two-way ANOVA. The results of the formulations arepromising when compared to a commercial tooth paste. Conclusion: This formulation prevented the growthof S. mutans and S. aureus, organisms causing dental caries. This formulation maintains oral hygiene therebypreventing gingivitis and dental caries.